Maternal Health Factors as Risks for Postnatal Depression: A Prospective Longitudinal Study. - Catherine L Chojenta; Jayne C Lucke; Peta M Forder; Deborah J Loxton (PLoS ONE, 2016)
PURPOSE:While previous studies have identified a range of potential risk factors for postnatal depression (PND), none have examined a comprehensive set of risk factors at a population-level using data collected prospectively. The aim of this study was to explore the relationship between a range of factors and PND and to construct a model of the predictors of PND. METHODS:Data came from 5219 women who completed Survey 5 of the Australian Longitudinal Study on Women's Health in 2009 and reported giving birth to a child. RESULTS:Over 15% of women reported experiencing PND with at least one of their children. The strongest positive associations were for postnatal anxiety (OR = 13.79,95%CI = 10.48,18.13) and antenatal depression (OR = 9.23,95%CI = 6.10,13.97). Positive associations were also found for history of depression and PND, low SF-36 Mental Health Index, emotional distress during labour, and breastfeeding for less than six months. CONCLUSIONS:Results indicate that understanding a woman's mental health history plays an important role in the detection of those who are most vulnerable to PND. Treatment and management of depression and anxiety earlier in life and during pregnancy may have a positive impact on the incidence of PND.